Study of the influence of venturi weir type on air bubble entrainment - Ozkan, Fahri; Kaya, Turgut; Baylar, Ahmet (Academic Journals, 2009)
Aeration is a natural or mechanical process of increasing the contact between water and air for the purpose of releasing entrained gases, adding oxygen, and improving the chemical and physical characteristics of water. Hydraulic structures can be accepted as the key components in improving aeration efficiency because of the strong turbulent mixing associated with substantial air bubble entrainment at these structures. Weir is the most classic example of a hydraulic structure where aeration occurs and the aeration properties of such a structure has been widely studied in the laboratory and field over a number of years. The present paper investigates the effect of the venturi weir type on air-demand ratio. The results indicate that the venturi weirs are highly effective in terms of air-demand ratio but however, the venturi weir type do not have a significant effect on air-demand ratio. Moreover, regression equations are obtained for the venturi weirs relating air-demand ratio to jet Froude number.
Keywords: Aeration; air-demand ratio; venturi; weir